INFLUENCE OF THE HASHTAG CONTEXT ON PUBLIC OPINION FORMATION ON SOCIOPOLITICAL ISSUES IN KENYA - Munuku, Anne Wangari; Mberia, Prof. Hellen; Ndavula, Dr. John (Journal of Public Policy and Administration, 2017)
Purpose: The purpose of the study was to determine how the context in which a hashtag is formulated the influences public opinion formation on sociopolitical issues in Kenya Methodology: The study adopted descriptive and qualitative research design. The study population consisted of the hashtags generated by Kenyans in the period between January 2014 and December 2016 and the local television stations and members of public involved in hashtag development outside the media fraternity. The sampling frame was obtained from the Communication Authority 2015 report, the Kenya Advertisers Association website and the Twitter database. Purposive sampling was used to select the 35 hashtags and snowball sampling was used to select the hashtag developers. Results: The study found that hash tag context has a significant relationship with public opinion formation. The study found that all hashtags formulated by Kenyans were context bound as they were formed whenever an issue rose. The wording of the hashtag (frame of communication) communicated the issue regime and the opinion of the formulator. The findings revealed that hashtags based on political contexts were more and trended longer. The political hashtags were 51% while social based ones stand at 40%. The rest were from security and economic contexts. Unique contribution to theory, practice and policy: The research draws on public opinion theory, the theory participatory communication theory and the Critical Discourse Analysis approach by Fairclough. The formulation and dissemination of news using hashtags is a growing and fast changing phenomenon that requires a new approach in its analysis. The use of these three approaches indicates the complexity of the nature of hashtags and the connection between the hashtag, the context that surrounds its formation and the opinion formed in relation to that context. The concept of citizen journalism must be looked at afresh.